Birth control in context: A case study of urban Egyptian women - Ezzat, Farida (AUC Knowledge Fountain, 2017)
Contraceptive choices, as a reflection of agency, inform us about various ways individual women seek particular forms of empowerment, in light of socio-economic, affective, and gender-based constraints. Ultimately, this serves to challenge inflexible conceptualizations of the status of women by calling into question the claim that patriarchy is unequivocally coercive and that women are inescapably disempowered and providing new avenues from where we may begin to rethink female agency and empowerment.